Effect of game format on heart rate, activity profile, and player involvement in elite and recreational youth players - Randers, M. B.; Andersen, T. B.; Rasmussen, L. S.; Larsen, M. N.; Krustrup, P. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The purpose of this study was to evaluate activity profile, aerobic load, and player involvement in two game formats of recreational and elite youth football for two age groups. A total of 152 youth players participated, with 45 U10 players playing 5v5 and 8v8 games, and 41 U13 players playing 8v8 and 11v11 (20 min) games. Activity profile, heart rate (HR), and technical actions were measured during all games using 10 Hz GPS, video filming, and HR monitors. For U10, no difference was found in total distance covered (1754 ± 237 vs 1771 ± 314 m, P = 0.650, d = 0.06), whereas mean HR (174 ± 10 vs 168 ± 12 bpm, P = 0.001, d = 0.59) and number of technical actions (65.1 ± 24.0 vs 36.9 ± 20.4, P < 0.001, d = 1.27) were higher in 5v5 than in 8v8. For U13, lower total distance covered (1821 ± 325 vs 2038 ± 328 m, P < 0.001, d = 0.66) and higher number of technical actions (36.2 ± 14.9 vs 26.9 ± 14.1, P < 0.001, d = 0.64) were observed in 8v8 than in 11v11, with no difference in mean HR (170 ± 10 vs 171 ± 10 bpm, P = 0.679, d = 0.10). In conclusion, HR is high in youth football matches irrespective of the level of play and the game format. Playing with fewer players on smaller pitches results in minor changes to the physical loading but elevates the technical involvement of youth players both at elite level and recreational level.